2011
DOI: 10.1002/wsb.81
|View full text |Cite
|
Sign up to set email alerts
|

White‐tailed deer age ratios as herd management and predator impact measures in pennsylvania

Abstract: A review of the Pennsylvania Game Commission's (PGC) deer management program and public concern about predator impacts on deer (Odocoileus virginianus) populations compelled the PGC to investigate the role of age ratios in developing management recommendations. Age ratios, such as proportion of juveniles in the antlerless harvest, may provide an index to population productivity and predator impacts. We estimated proportion of juveniles in the antlerless harvest from hunter-killed deer, population trends using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The range expansion of coyotes has fueled concerns of many stakeholder groups that increased predation pressure by coyotes is having an adverse effect on white‐tailed deer populations. For example, hunters in Pennsylvania and New York voiced concerns about coyote predation through comments at public meetings, lawsuits to halt antlerless harvest in Pennsylvania, and requests for fewer antlerless deer permit allocations (J. Hurst, New York State Department of Environmental Conservation, personal observation; Rosenberry et al ). Many members of the public, as well as politicians and some wildlife biologists, have suggested that more fawn survival studies be undertaken and that bounties for predators should be implemented (Rosenberry et al ), even though there is little evidence of declines in deer populations concurrent with coyote range expansion (McShea ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The range expansion of coyotes has fueled concerns of many stakeholder groups that increased predation pressure by coyotes is having an adverse effect on white‐tailed deer populations. For example, hunters in Pennsylvania and New York voiced concerns about coyote predation through comments at public meetings, lawsuits to halt antlerless harvest in Pennsylvania, and requests for fewer antlerless deer permit allocations (J. Hurst, New York State Department of Environmental Conservation, personal observation; Rosenberry et al ). Many members of the public, as well as politicians and some wildlife biologists, have suggested that more fawn survival studies be undertaken and that bounties for predators should be implemented (Rosenberry et al ), even though there is little evidence of declines in deer populations concurrent with coyote range expansion (McShea ).…”
mentioning
confidence: 99%
“…For example, hunters in Pennsylvania and New York voiced concerns about coyote predation through comments at public meetings, lawsuits to halt antlerless harvest in Pennsylvania, and requests for fewer antlerless deer permit allocations (J. Hurst, New York State Department of Environmental Conservation, personal observation; Rosenberry et al ). Many members of the public, as well as politicians and some wildlife biologists, have suggested that more fawn survival studies be undertaken and that bounties for predators should be implemented (Rosenberry et al ), even though there is little evidence of declines in deer populations concurrent with coyote range expansion (McShea ). However, predation on neonate white‐tailed deer was the probable cause of recent population declines in South Carolina, prompting recommendations that coyote predation effects on neonate deer be taken into account when setting harvest management goals, regardless of deer population trends (Kilgo et al , ).…”
mentioning
confidence: 99%
“…Aerial surveys, though costly, can provide a reliable recruitment index where habitat conditions are amenable (Koerth et al 1997, Rabe et al 2002. Harvest ratio of fawns: does can provide a reasonable index of recruitment, although care must be taken to account for possible bias (Roseberry and Klimstra 1974, Coe et al 1980, Roseberry and Woolf 1991, Rosenberry et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The political element is a formalization of societal values in wildlife governance; it defines the roles and authority of wildlife management agencies and often bounds management decisions through laws, policies, statutes, budget allocation, or agency directives (Decker et al 2016). The political element can also influence decision making when well‐thought‐out management decisions that have considered the array of stakeholder interests are overridden for political reasons, such as the results being unpopular with one or more politically influential special‐interest groups (Loker et al 1994, Rosenberry et al 2011). Finally, the ecological element of the social–ecological system defines the biophysical state of the system under question.…”
mentioning
confidence: 99%